2002
DOI: 10.1046/j.1365-2796.2002.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and prevention of hepatitis C in dialysis patients and renal transplant recipients. A long‐term follow up (1989–January 1997)

Abstract: Abstract. Almroth G, Ekermo B, Ma Ênsson A-S,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Epidemiological and molecular studies have shown the role of the hemodialysis environment for dissemination of HCV between patients (Djordjevic et al 2000, Schneeberger et al 2000, Almoroth et al 2002, Bdour 2002, Furusyo et al 2004, Sartor et al 2004). In our investigation, length of time on hemodialysis was independently associated with anti-HCV positivity in all period investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological and molecular studies have shown the role of the hemodialysis environment for dissemination of HCV between patients (Djordjevic et al 2000, Schneeberger et al 2000, Almoroth et al 2002, Bdour 2002, Furusyo et al 2004, Sartor et al 2004). In our investigation, length of time on hemodialysis was independently associated with anti-HCV positivity in all period investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, prevalence rates varying from 13% (Souza et al 2003) to 64.7% (Vanderborght et al 1995) have been reported. The screening of anti-HCV in blood banks and the adoption of hemodialysis-specific infection control measures have been implicated in the declining of HCV infection in hemodialysis patients (Djordjevic et al 2000, Almoroth et al 2002, Valtuille et al 2002. In our country, the first measure has been implemented since November 1993, and the latter in the end of 1996 in compliance with news Health Ministry Standards for Renal units which are in accordance with most of Centers for Disease Control and Prevention (CDC 2001) recommendations.…”
mentioning
confidence: 99%
“…Several recent studies [31, 52, 54, 59, 65, 79,143,144,145,146,147,148,149,150] and one large study [44] reported nosocomial patient-to-patient transmission of HCV infection among HD patients performing phylogenetic analysis of HCV viral isolates. Although the potential sources of nosocomial transmission could be dialyzer reuse, internal contamination of HD monitors, and contaminated hands and articles, the two former mechanisms are almost unlikely [92, 93, 151, 152].…”
Section: Evidence Of Nosocomial Transmission and Preventive Strategiesmentioning
confidence: 99%
“…Mello Lde et al [23] , 2007 Lopes et al [24] , 2006 Albuquerque et al [25] , 2005 Carneiro et al [26] , 2001 China Maintain 7.01%-37.34% Ren et al [27] , 2011 Qi et al [28] , 2003 Greece 10%-29% Garinis et al [29] , 1999 Rigopoulou et al [30] , 2005 Sypsa et al [31] , 2005 Sweden 11.0% Almroth et al [32] , 2002 Iran 13.2% Alavian et al [33] , 2003 France 16.3% Salama et al [34] , 2000 Tunisia 19%-41.7% Bouzgarrou et al [35] , 2005 Ayed et al [36] , 2003 Libya 20.5% Daw et al [37] , 2002…”
Section: Risk Factorsmentioning
confidence: 99%